Cost-effectiveness of Direct Oral Anticoagulant vs. Warfarin Among Atrial Fibrillation Patients With Intermediate Stroke Risk - Choi, Ju Hee; Kim, Woojin; Kim, Yun Tae; Cho, Jaelim; Shin, Seung Yong; Kim, Changsoo; Kim, Jin-Bae (Frontiers in Cardiovascular Medicine, 2022)
Background: Several studies have shown the cost-effectiveness of direct oral anticoagulants (DOACs), compared with warfarin, to prevent atrial fibrillation (AF) related complications. However, few have reported cost-effectiveness of DOACs in AF patients with intermediate stroke risk. Thus, we investigated the cost-effectiveness of DOACs versus warfarin in non-valvular AF patients with intermediate stroke risk using national representative data. Methods: We identified 7,413 newly diagnosed non-valvular AF patients (≥ 18 years) with intermediate stroke risk (CHA2DS2-VASc score: 1 for men and 2 for women) using the national healthcare utilization data from August 1, 2016, to July 31, 2019. Annual incidence rate of AF-related composite outcomes (heat failure, myocardial infarction, ischemic stroke, intracerebral hemorrhage, and gastrointestinal bleeding) was estimated. Cost-effectiveness was estimated using a Markov chain model with the transition probability of one year. The willingness-to-pay (WTP) was set at $32,000 per quality-adjusted life-year (QALY) gained. Results: The total cost of warfarin, rivaroxaban, apixaban, dabigatran and edoxaban was $2,874, $5,761, $5,151, $5,761 and $5,851, respectively. The QALYs gained were 10.83, 10.95, 11.10, 10.49 and 10.99 years, respectively. The incremental cost-effectiveness ratio of rivaroxaban, apixaban, dabigatran and edoxaban was $29,743.99, $8,426.71, -$8,483.04 and $18,483.55, respectively. The WTP was set at $32,000. DOACs (except dabigatran) were more cost-effective compared with warfarin because they did not exceed the WTP in the base-case analysis. Conclusion: Our findings showed that DOACs were more cost-effective than warfarin in non-valvular AF patients with intermediate stroke risk.